The GreenSeeker Handheld: A Research Brief on Farmer Technology Adoption and Disadoption - Lapidus, Daniel; Latané, Annah; Ortíz Monasterio, Jose Iván; Beach, Robert H.; Cárdenas Castañeda, María Elena (RTI Press, 2017)
The GreenSeeker Handheld crop sensor is an innovative diagnostic tool that farmers can use to improve their fertilizer use efficiency. Over the last decade, farmers in the Yaqui Valley, Sonora, Mexico, widely adopted the technology. Adoption led to significant increases in profits for farmers as well as avoided greenhouse gas emissions. Despite this success, adoption declined sharply in the 2015–2016 growing season. RTI researchers collaborated with the International Wheat and Maize Improvement Center (CIMMYT) to analyze the average costs and benefits of use of the GreenSeeker in addition to the amount of reductions in greenhouse gas emissions. We provide the initial results of these analyses and lessons learned that can help inform dissemination of sustainable agricultural technology transfer.